Empowerment of posyandu lansia cadres in overcoming depression and violence among elderly women after the COVID-19 pandemic in Dukuh Panggungan - Yudani, Alfi Fatima; Pratiti, Budi; DW, Sumarni; Probosuseno, Probosuseno; Purwanta, Purwanta (Journal of Community Empowerment for Health, 2024)
Introduction: The COVID-19 pandemic has significantly impacted the mental health and safety of the elderly, particularly affecting elderly women. Research indicates a rise in anxiety and depression among older adults, with pre-existing elevated depressive symptoms exacerbating their resilience during this period. Increased isolation, financial strain, and restricted access to support services have led to a surge in elder abuse cases, disproportionately affecting women. Effective strategies, such as raising awareness and ensuring timely provision of resources, are crucial to safeguarding the mental well-being of the elderly. Indonesia's commitment to sustainable development and health equity, exemplified through initiatives like the Sustainable Development Goals, must address the specific challenges faced by elderly women in communities like Panggungan Village. The demographic shift towards an aging population, coupled with the pandemic's effects, further magnifies vulnerabilities. Empowering community-based resources can provide holistic support to elderly women, contributing to sustainable health development and social equity. Methods: The approach targets 15 Posyandu Lansia cadres and 20 elderly women in Panggungan Village through an offline community service program adhering to health protocols. Tools used in this study were the Mental Health Improvement Module, Geriatric Depression Scale questionnaire, and knowledge/skills assessment for Posyandu Lansia cadres. A combined quantitative and qualitative analysis was applied. Results: Results showed that 55% prevalence of verbal violence, 45% neglect, and 35% exploitation violence among elderly women. Post-training, these figures improved to 25% for verbal violence, 10% for exploitation violence, and 15% for neglect violence. Depression tendencies witnessed a 25% shift. Cadres’ knowledge increased from 58.2 to 82.1, and skills improved from 63.5 to 79.2. Conclusion: Elevated violence and depression tendencies that were quite high, negatively impact elderly women's mental health in Panggungan Village. Cadre’s training significantly enhances residents' well-being and mental health, offering a meaningful solution.